FINANCIAL LITERACY AND FINANCIAL SELF-EFFICACY AND THEIR INFLUENCE ON RISKY CREDIT BEHAVIOR USING SHOPEE PAY LATER (STUDY ON GENERATION Z IN PEKANBARU CITY) - Damayanti, Umi Rachmah (Economic and Science Faculty of Islamic State University, 2025)
Risky Credit Behavior refers to the use of consumer credit in ways that may negatively impact future financial stability. This study examines how financial literacy and financial self-efficacy influence risky credit behavior when using Shopee PayLater among Generation Z in Pekanbaru City. The research employs multiple linear regression analysis, including reliability and validity tests, classical assumption tests, and hypothesis testing. Using a quantitative descriptive approach, the study gathers data from 632 eligible Generation Z respondents in Pekanbaru. The results indicate that both financial literacy and self-efficacy significantly affect risky credit behavior in Shopee PayLater usage. The adjusted R-squared value of 0.105 (10.5%) suggests that these two factors explain 10.5% of the variation in risky credit behavior